Separating wheat and chaff: age-specific staffing strategies and innovative performance at the firm level - Katharina Frosch; Christian Göbel; Thomas Zwick (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
Adopting a dynamic perspective, this paper investigates age-related staffing patterns in German establishments and their effect on innovative performance. First, we investigate how establishments achieve the necessary workforce rejuvenation - from the inflow of younger or from outflows of older workers. In addition, we explore whether certain staffing patterns are more likely to appear under different economic regimes. In a second step, we analyze whether an establishment's innovative performance is related to the staffing patterns it experiences. The analysis of linked-employer-employee data shows that most of the 585 German establishments covered rejuvenate by inflows of younger workers. Half of the establishments also use the outflow of older workers. Furthermore, workforces are more likely to become more age-heterogeneous in growing establishments. Finally, we do not find evidence that a youth-centered human resource strategy (always) fosters innovation.
Keywords: 330; Personalpolitik; altersspezifische Faktoren; human resource management; Innovationsfähigkeit; Beschäftigtenstruktur; Altern; Personaleinstellung; Entlassungen; IAB-Linked-Employer-Employee-Datensatz; Altersstruktur; ältere Arbeitnehmer